In vivo flow cytometer for real-time detection and quantification of circulating cells - Novak, J. (2004)
An in vivo flow cytometer is developed that allows the real-time detection and quantification of circulating fluorescently labeled cells in live animals. A signal from a cell population of interest is recorded as the cells pass through a slit of light focused across a blood vessel. Confocal detection of the excited fluorescence allows continuous monitoring of labeled cells in the upper layers of scattering tissue, such as the skin. The device is used to characterize the in vivo kinetics of red and white blood cells circulating in the vasculatúre of the mouse ear. Potential applications in biology and medicine are discussed.